The pesticide mineralization capacity in sand filter units of drinking water treatment plants (DWTP): Consistency in time and relationship with intake water and sand filter characteristics. (August 2019) - Vandermaesen, Johanna; Horemans, Benjamin; Degryse, Julie; Boonen, Jos; Walravens, Eddy; Springael, Dirk
Abstract: Sand filters (SFs) are commonly applied in drinking water treatment plants (DWTPs) for removal of iron and manganese but also show potential for microbial degradation of pesticide residues. The latter is advantageous in case the intake water contains pesticide residues. However, whether this involves mineralization suggesting no generation of harmful transformation products, its consistency over time, and how this ability relates to physicochemical and biological characteristics of the DWTP intake water and the SFs is unknown. The capacity to mineralize the herbicides bentazon and 2-methyl-4-chlorophenoxyacetic acid (MCPA) was examined in SF samples from 11 DWTPs differing in operation, intake water composition and pesticide contamination level. MCPA was mineralized in all biologically active SFs while mineralization of bentazon occurred rarely. Mineralization of both compounds was consistent in time and across samples taken from different SF units of the same DWTP. Kinetic modelling of mineralization curves suggested the occurrence of growth linked bentazon and MCPA mineralization in several SF samples. Multivariate analysis correlating intake water/SF characteristics with pesticide mineralization indicated that pesticide mineralization capacity depended on a range of intake water characteristics, but was not necessarily explained by the presence of the pesticide in the intake water and hence the in situ exposure of the SF community to the pesticide. This was supported by testing a sample from DWTP Kluizen for its capacity to mineralize 5 other pesticides including pesticides not present or occasionally present in the intake water. All of those pesticides were mineralized as well. Highlights: Microbial communities in SFs of DWTPs mineralize pesticide residues. MCPA was readily mineralized in all biologically active SFs. Bentazon was rarely mineralized, but its mineralization capacity was consistent. Pesticide mineralization capacity cannot be explained by the in situ exposure of the SF community to the pesticide.